Hubungan Pendidikan Ibu dan Ekonomi Keluarga Pada Pertumbuhan Balita di Puskesmas Pemulutan - Arly Febrianti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2018)
Child growth is the increase in the number, size of an organ and the development of the ability (skill) of complex and regular body functions. Many factors influence, one of which is family factor. Growth will be optimal if the various factors of the family is improved, both in terms of quantity and quality. The problem in this research is the unknown relationship of mother education level and family economic level on the growth of children under five (1-5 years) at Puskesmas Pemulutan of Ogan Ilir Regency covering dependent variable and independent variable. The purpose of this study is to determine the relationship between maternal education level and family economic level on the growth of children under five years (1-5 years) in Puskesmas Pemulutan Ogan Ilir District. This research is a descriptive analytic research with cross sectional approach to know the relationship of education level of mother and the economic level of the family on the growth of children under five (1-5 years) conducted on 50 samples by using the total population of mothers with children aged 1-5 years in Puskesmas Pemulutan Ogan Ilir. In this study, it was found that 50 mothers with children aged 1-5 years of education owned by the mother percentage were not much different from the well-educated mothers (53.0%), (70.0% ) family income is low, and the growth of children in Puskesmas Pemulutan is normal (62.0%). From the research results found that there is a relationship between the level of education of the mother and the economic level of the family with the growth of children. Therefore, it is recommended that health workers and posyandu cadres are more active in providing information, counseling, and early detection of child development